2008
DOI: 10.1021/cg8003905
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Controlled Assembly of Manganese(II) Tetrachloroterephthalates with 1D Chain, 2D Layer, and 3D Coordination Architectures

Abstract: With solvent molecules participating in coordination systems, four new Mn II coordination polymers of the rigid ligand 2,3,5,6-tetrachloro-1,4-benzenedicarboxylic acid (H 2 BDC-Cl 4 ) have been obtained from different solvent media. Singlecrystal X-ray analysis indicates that the coordination arrays of 1-4 vary from 1D fishbone or zigzag chain for 1 or 2, 2D (4,4) layer for 3, to 3D SrAl 2 coordination network for 4, respectively. In {[Mn(BDC-Cl 4 )(py) 2 (H 2 O) 2 ](py) 2 } n (1) and {[Mn(BDC-Cl 4 )(MeOH) 3 ]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 135 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…Recent studies have shown the remarkable analogy of 1,4-BDC-type ligands with bulky methyl [4], fluorine [5], chlorine [6] or bromine [7] groups, since they not only provide astonishing thermal and chemical stability and stereo-chemical characteristics, but also prevent interpenetration phenomena of resultant polymeric networks. In the asymmetric unit, one Zn II ion lying on an inversion center [at (0 0 ½)] is coordinated by six oxygen atoms in anearly ideal octahedral configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the remarkable analogy of 1,4-BDC-type ligands with bulky methyl [4], fluorine [5], chlorine [6] or bromine [7] groups, since they not only provide astonishing thermal and chemical stability and stereo-chemical characteristics, but also prevent interpenetration phenomena of resultant polymeric networks. In the asymmetric unit, one Zn II ion lying on an inversion center [at (0 0 ½)] is coordinated by six oxygen atoms in anearly ideal octahedral configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Among the widely used organic solvents, DMF was proved to be a reliable binding guest molecule participating in coordination networks of Mn II and Cu II ions [29,30]. Its coordinating ability is better than that of EtOH, MeOH and the aqua ligand in mixed solvent media.…”
Section: Synthesis and General Characterizationmentioning
confidence: 99%
“…Concurrently, the low-dimensional CPs could extend to 3D supramolecular network by hydrogen bonds and π-π aromatic interactions, which play key roles on the generation of novel supramolecular structures. [34][35][36] In this paper, a 1D zigzag chain CPs [Cd(HL)(H 2 O) 3 Single-crystal X-ray Diffraction Determination: The crystal structures were determined by single-crystal X-ray diffraction. The X-ray intensity data for the four compounds were collected with a computercontrolled Oxford Xcalibur E diffractometer with graphite monochromatic Mo-K α radiation (λ = 0.71073 Å) at 298 K. Final unit cell parameters were derived by global refinements of reflections obtained from integration of all the frame data.…”
Section: Introductionmentioning
confidence: 99%